High Prevalence of Male Sexual Dysfunction in a Prospective Multicenter VA Inflammatory Bowel Disease Population. Issue 1 (13th February 2020) - Gaidos, Jill K J; Naik, Katrina; Dave, Jenny; Yao, Michael; Hou, Jason K; Cipher, Daisha J; Smith, Andrew D; Feagins, Linda A
Abstract: Background: Aims of this study were to assess the prevalence of and risk factors for sexual dysfunction (SD) in male veterans with inflammatory bowel disease (IBD). Methods: We collected IBD history, quality of life (QOL), and sexual function surveys. Results: One hundred seventy-one men enrolled, mean age 50 years, 85% had SD, 92% had erectile dysfunction (ED). More severe ED ( P = 0.0001), decreased sexual desire ( P = 0.004), and decreased satisfaction ( P = 0.001) were associated with poorer QOL. Biologic use was associated with increased SD; hypertension with a decrease in sexual desire. Conclusions: SD and ED are highly prevalent and associated with poorer QOL. Lay Summary: Sexual health has not been well defined in male patients with inflammatory bowel disease. In this multicenter study, 85% had sexual dysfunction with increased odds in those with hypertension and biologic use. Sexual dysfunction correlated with decreased quality of life.